REFERENCE ANATOMICAL STRUCTURES TO PERFORM A CRANIOTOMY IN THE PIG - Torres G., Juan Pablo (2008)
The objective of this study was to determine the anatomic reference points to perform a craniotomy in pigs. Forty four heads of Landrace, Pietrain, and creole pigs of 22-89 kg of body weight (males = 2, females = 22, castrated males = 20) were used. The four anatomic points under evaluation were P1: at a distance “a” from the external occipital protuberance (OP) to cranial; P2: at a distance “b” from the OP point to cranial; P3 and P4: equidistant, at a distance “c” to intersection point formed by imaginaries lines between supraorbitary apophysis (SA) and the frontal bones half line (LmhF). A 11 mm perforation drilling (cutting) was used in order to enter inside P1 and P2, and a hand piece was used for P3 and P4. The variables under evaluation were the length between the OP to the end of the nose, between both AS, P1 depth, between P1 and P3-P4, P2 and P3-P4. No statistical difference between castrated males and females was found. It is recommended four anatomic reference points to perform a craniotomy in the pig: P1 in females and castrated males was at 2.73 and 2.98 cm from OP respectively; P2 in females and castrated males was 7.72 and 7.51 cm respectively; and P3 and P4 at 3.8 cm from the intersection point formed by imaginaries lines between SA and the LmhF.